2021
DOI: 10.1186/s43055-020-00404-x
|View full text |Cite
|
Sign up to set email alerts
|

Fractional anisotropy measurements of the left dorsolateral prefrontal cortex for therapeutic response assessment after repetitive transcranial magnetic stimulation (rTMS) in relapsing remitting multiple sclerosis patients suffering from depression

Abstract: Background Multiple sclerosis (MS) is a major cause of neurological disability in adults. Depression is one of the most common psychiatric comorbidities in MS patients with negative impact on patients’ quality of life. The aim of the study is to evaluate the role of diffusion tensor imaging (DTI) in monitoring the therapeutic response after high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) versus selective serotonin reuptake inhibitor (SSRI) therapy for relapsing remitting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
16

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 27 publications
0
3
0
16
Order By: Relevance
“…Compromised WM integrity in the splenium may represent not only a biomarker, but also a therapeutic target. Notably, excitatory repetitive transcranial magnetic stimulation was found to induce increases in WM FA in various conditions, such as depression ( Hassan et al, 2021 ) and stroke ( Allendorfer et al, 2012 ). It has been suggested that the observed amelioration of illness awareness in schizophrenia after neuro-stimulation is caused by restored hemispheric balance ( Chang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compromised WM integrity in the splenium may represent not only a biomarker, but also a therapeutic target. Notably, excitatory repetitive transcranial magnetic stimulation was found to induce increases in WM FA in various conditions, such as depression ( Hassan et al, 2021 ) and stroke ( Allendorfer et al, 2012 ). It has been suggested that the observed amelioration of illness awareness in schizophrenia after neuro-stimulation is caused by restored hemispheric balance ( Chang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente se incluyeron 25 ensayos clínicos (28 referencias) que analizaban los resultados de la EMT en el tratamiento de pacientes con EM: 15 ensayos clínicos finalizados (17 referencias) [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] y otros 10 estudios en marcha [104][105][106][107][108][109][110][111][112][113][114] (11 referencias). Los principales datos de los estudios en marcha pueden consultarse en el Anexo 4.…”
Section: Resultsunclassified
“…Los 15 ensayos clínicos [87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] incluidos analizaron un total de 352 pacientes, de los cuales 207 (58,8%) fueron sometidos a alguna modalidad de EMT y 145 (41,2%) a otro tipo de intervenciones como comparadores. El diseño de la mayor parte (n=10) de los estudios incluidos fue el de ensayo clínico aleatorizado de brazos paralelos, mientras que entre los restantes 5 estudios, tres de ellos fueron no aleatorizados 87,90,96 y dos utilizaron un diseño de ensayo clínico cruzado 102,103 .…”
Section: Características De Los Estudios Incluidosunclassified
See 2 more Smart Citations